1996
DOI: 10.1126/science.274.5293.1744
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Endothelial NO Synthase in LTP Revealed by Adenovirus-Mediated Inhibition and Rescue

Abstract: Pharmacological studies support the idea that nitric oxide (NO) serves as a retrograde messenger during long-term potentiation (LTP) in area CA1 of the hippocampus. Mice with a defective form of the gene for neuronal NO synthase (nNOS), however, exhibit normal LTP. The myristoyl protein endothelial NOS (eNOS) is present in the dendrites of CA1 neurons. Recombinant adenovirus vectors containing either a truncated eNOS (a putative dominant negative) or an eNOS fused to a transmembrane protein were used to demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(109 citation statements)
references
References 19 publications
5
104
0
Order By: Relevance
“…Our studies suggest that uninjured iNOS -/-mice perform normally in motor and spatial memory acquisition tasks compared with wild-type mice. This argues against an essential role for iNOS in the events involved in completing these behavioral tasks, as was seen for eNOS in long-term potentiation (46)(47)(48), and argues strongly against a nonspecific functional deficit in our mutant mice (49).…”
Section: Figurementioning
confidence: 91%
“…Our studies suggest that uninjured iNOS -/-mice perform normally in motor and spatial memory acquisition tasks compared with wild-type mice. This argues against an essential role for iNOS in the events involved in completing these behavioral tasks, as was seen for eNOS in long-term potentiation (46)(47)(48), and argues strongly against a nonspecific functional deficit in our mutant mice (49).…”
Section: Figurementioning
confidence: 91%
“…lial NOS (eNOS) is localized to the membrane by myristolation (Busconi and Michel, 1993), whereas neural NOS (nNOS) can be linked to the NMDA receptor by postsynaptic density-95 (Brenman et al, 1996). Previous studies have implicated both eNOS (Kantor et al, 1996;Haul et al, 1999) and nNOS (Son et al, 1996) in LTP. Recent evidence from cultured hippocampal cells has also shown that NO may have both presynaptic and postsynaptic effects (Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate purification of the protein using glutathione-Sepharose affinity chromatography, we used the bacterial expression vector pGEX-3X (Pharmacia) to construct a recombinant plasmid encoding a fusion protein between eNOS and GST. The fusion protein was designed such that the GST is located at the eNOS N terminus; this site was chosen because previously characterized eNOS fusion proteins involving the enzyme's N terminus appear to retain full activity (20). Indeed, the specific activity of the purified bacterially expressed GST-eNOS fusion protein averaged 50 nmol/min/mg protein (see Fig.…”
Section: Bacterial Expression Of Recombinant Enos and Inhibition Of Tmentioning
confidence: 99%